2014
DOI: 10.1155/2014/865839
|View full text |Cite
|
Sign up to set email alerts
|

Study of Tribological Properties of Nanolamellar WS2 and MoS2 as Additives to Lubricants

Abstract: This work was aimed at studying the tribological properties of nanolamellar tungsten and molybdenum disulfides produced from nanosized W and Mo nanopowders by self-propagating high-temperature synthesis. The prepared WS2and MoS2powders were examined by scanning electron microscopy (SEM), X-ray diffraction (XRD), and differential thermal analysis (DTA). For tribological tests, oil-based lubricants added with nanolamellar tungsten and molybdenum disulfides were prepared. The tribological tests show that the fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 21 publications
(22 reference statements)
1
33
0
Order By: Relevance
“…In recent years, the preparation methods of MoS 2 /WS 2 nanoparticles have been extensively studied. The researchers have successfully prepared MoS 2 /WS 2 nanoparticles through various synthetic methods and discussed their tribological properties under different experimental environments [5][6][7]. Among them, inorganic fullerene-like (IF) MoS 2 /WS 2 nanoparticles seem to be the most widely explored ones, probably because of their low surface energy, fine chemical stability, and spherical shape, which allow them to play an active role in a variety of tribological applications [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the preparation methods of MoS 2 /WS 2 nanoparticles have been extensively studied. The researchers have successfully prepared MoS 2 /WS 2 nanoparticles through various synthetic methods and discussed their tribological properties under different experimental environments [5][6][7]. Among them, inorganic fullerene-like (IF) MoS 2 /WS 2 nanoparticles seem to be the most widely explored ones, probably because of their low surface energy, fine chemical stability, and spherical shape, which allow them to play an active role in a variety of tribological applications [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of using oil additives is to keep the ultra-low COF even under mixed lubrication conditions when asperities of the counter-bodies come into direct contact with each other [2]. This usually is achieved by crystallographically aligned solid lubricant films of either graphite [5][6][7] or MoS 2 and WS 2 [8][9][10][11][12], or by amorphous films which can flow in a fluid-like manner [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al [14] studied the tribological behaviors of graphite nanoparticles as mineral oil additive using a disc-on-disc tribotester and found that the improvement in friction-reducing and antiwear properties of pure oil was attributed to the presence of spherical nanoparticles, which prevented direct contact between frictional surfaces. An et al [15] produced nanolamellar tungsten and molybdenum Table 1: Properties of graphite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%